HPV genotype is a prognosticator for recurrence of respiratory papillomatosis in children - Nogueira, Rodrigo L.; Küpper, Daniel S.; do Bonfim, Caroline M. [UNESP]; Aragon, Davi C.; Damico, Thiago A.; Miura, Carolina S.; Passos, Ivna M.; Nogueira, Maurício L.; Rahal, Paula [UNESP]; Valera, Fabiana C. P. (Wiley, 2021)
Objectives: This study aimed to compare the prognosis according to age, genotype or human papillomavirus (HPV) variant in patients with recurrent respiratory papillomatosis (RRP). Design: Non-concurrent cohort. Participants: Forty one patients with RRP. Setting: Tertiary referral hospital. Main Outcome Measures: Disease severity was defined by the number of surgeries performed, and Derkay score at surgeries, obtained from medical records. HPV was detected and genotyped, and HPV-6 variants were also assessed. Results: Fifteen (36.58%) individuals belonged to the juvenile RRP group (JoRRP, less than 18 years), while 26 patients (63.41%) were allocated at the adult group (AoRRP, equal or more than 18 years). JoRRP patients needed, in average, a higher number of surgeries to control the disease than AoRRP patients (mean difference: 3.36). Also, JoRRP patients showed a higher Derkay score at each surgery (mean difference: 3.76). There was no significant difference in the number of surgeries when we compared patients infected with HPV-6 or HPV-11, neither in accordance to HPV-6 variants. Patients with HPV-11 presented a higher mean Derkay score at surgery than those with HPV-6 (mean difference: 4.39); when co-variated by age, we observed that this difference occurred only among JoRRP patients (mean difference: 6.15). Conclusions: Age of onset of RRP has an important impact on number of surgeries to control disease. Patients with JoRRP and HPV-11 tend to present worse Derkay score at each surgery. HPV genotype among adults and HPV-6 variants had no impact on the outcome of the disease.
Keywords: human papillomavirus; outcome; recurrent respiratory papillomatosis; surgery; type; variant